2016
DOI: 10.1016/j.jsams.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Preventive interventions for tendinopathy: A systematic review

Abstract: There is limited evidence that a long-term intervention including balance training is effective in the prevention of patellar and Achilles tendinopathy. Shoe adaptations in the form of shock absorbing insoles could have a preventive effect on Achilles tendinopathy. Hormone replacement therapy seems to reduce the risk for structural Achilles tendon changes in active post-menopausal women. No evidence was found for a positive effect of stretching exercises. Prophylactic eccentric training and stretching can incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…The prevention or reduction of musculotendinous imbalances could, in our view, have beneficial effects on (a) the risk of tendon injury and (b) athletic performance. A recent systematic review on the effects of preventive interventions for tendinopathy concluded that evidence for their efficacy is only limited (Peters et al, 2016 ). However, the exercise interventions examined were either not targeting the improvement of the mechanical properties of the tendon (e.g., balance training, stretching) or did not apply training stimuli that are in accordance with the current view on the mechanobiological basis of human tendon adaptation in vivo (e.g., Alfredson eccentric training or Silbernagel's combined concentric-eccentric exercise; Malliaras et al, 2013a for a discussion).…”
Section: Implications and Concepts For Preventionmentioning
confidence: 99%
“…The prevention or reduction of musculotendinous imbalances could, in our view, have beneficial effects on (a) the risk of tendon injury and (b) athletic performance. A recent systematic review on the effects of preventive interventions for tendinopathy concluded that evidence for their efficacy is only limited (Peters et al, 2016 ). However, the exercise interventions examined were either not targeting the improvement of the mechanical properties of the tendon (e.g., balance training, stretching) or did not apply training stimuli that are in accordance with the current view on the mechanobiological basis of human tendon adaptation in vivo (e.g., Alfredson eccentric training or Silbernagel's combined concentric-eccentric exercise; Malliaras et al, 2013a for a discussion).…”
Section: Implications and Concepts For Preventionmentioning
confidence: 99%
“…Although there is a wide range of tendon pathologies, it appears that the majority of overuse tendinopathies in athletes are due to tendinosis [2]. Tendinopathy has multifactorial etiology, but studies examining risk factors of tendinopathy show a lack of uniformity and statistical power [3]. Reliable, well-conducted epidemiological studies are not available for most tendinopathies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tendinopathy is a common condition that affects a large portion of the population, making up 30% of all musculoskeletal injuries 1 and being the most prevalent tendon disorder 2 . It is generally defined as an overuse injury resulting in tendon degeneration after a failed early inflammatory healing response 3 , leading to collagen disorientation and disorganization in the absence of classic inflammatory changes, accompanied by pain and dysfunction 4,5 .…”
mentioning
confidence: 99%